A Profusion of Molecular Scissors for Pectins: Classification, Expression, and Functions of Plant Polygalacturonases - Yang, Yang; Yu, Youjian; Liang, Ying; Anderson, Charles T.; Cao, Jiashu (Frontiers in Plant Science, 2018)
In plants, the construction, differentiation, maturation, and degradation of the cell wall are essential for development. Pectins, which are major constituents of primary cell walls in eudicots, function in multiple developmental processes through their synthesis, modification, and degradation. Several pectin modifying enzymes regulate pectin degradation via different modes of action. Polygalacturonases (PGs), which function in the last step of pectin degradation, are a crucial class of pectin-modifying enzymes. Based on difference in their hydrolyzing activities, PGs can be divided into three main types: exo-PGs, endo-PGs, and rhamno-PGs. Their functions were initially investigated based on the expression patterns of PG genes and measurements of total PG activity in organs. In most plant species, PGs are encoded by a large, multigene family. However, due to the lack of genome sequencing data in early studies, the number of identified PG genes was initially limited. Little was known about the evolution and expression patterns of PG family members in different species. Furthermore, the functions of PGs in cell dynamics and developmental processes, as well as the regulatory pathways that govern these functions, are far from fully understood. In this review, we focus on how recent studies have begun to fill in these blanks. On the basis of identified PG family members in multiple species, we review their structural characteristics, classification, and molecular evolution in terms of plant phylogenetics. We also highlight the diverse expression patterns and biological functions of PGs during various developmental processes, as well as their mechanisms of action in cell dynamic processes. How PG functions are potentially regulated by hormones, transcription factors, environmental factors, pH and Ca2+ is discussed, indicating directions for future research into PG function and regulation.